Hyoscyamine and scopolamine production in transformed root cultures of Datura metel L - Ahmad, Aziz (2000)
The transformed root cultures of Datura metel L (kecubung) was successfully established via Agrobacterium rhizogenes-mediated, which contained the pBI 121 plasmid harbouring the GUS and kanamycin coding genes. The transformation was biochemically confirmed with GUS assay indicated by the presence of blue spot on roots, Southern blotting and the resistance of transformed root to Kanamycin. Transformed roots were showed a typical character of transformed root, which is sensitive to exogenous IAA (auxin). Sustained root cultures appeared to produce hyoscyamine and scopolamine ten times higher than that produced in the intact plant. The ability of the transformed roots to produce hyoscyamine and scopolamine in different types of basal media used was examined. It was ubserved that Gamborg's B 5 basal medium was the best medium for root growth as well as the hyoscyamine and scopolamine production. Gamborg's B5 medium was used for subsequent studies. Among the carbon source tested, sucrose appeared to be the best carbon source for root growth. Consequently, the effect of Gamborg's B5 medium ionic strength and sucrose concentration was examined. Gamborg's BS medium was used in quarter, half and full strength, and supplemented with sucrose concentration in the range of 1 - to 8% (w/v). Full strength Gamborg' s B5 medium with 4% sucrose was observed to enhance the root growth as well as hyoscyamine and scopolamine production. Studies were also carried out to examine the effect of various concentrations of macro and microelements on root growth, hyoscyamine and scopolamine production. The macro elements used were nitrogen (ammonium and nitrate balance), magnesium, calcium and phosphate. Amongst the macro element tested, nitrogen, which is in the form of nitrate and/or ammonium, was found to have a significant effect on the hyoscyamine and scopolamine production. Meanwhile, the microelements that have been studied were copper, ferric, manganese, zinc and boron. Ferric and copper appeared to have the greater effect on hyoscyamine and scopolamine production than other elements. Roots cultured in medium with lower concentration of microelement than that present in Gamborg's B5 medium was also observed to enhance the hyoscyamine and scopolamine content. Feeding of each precursors i. e. putrescine, I-ornithine, arginine, 1-phenylalanine, hyoscyamine and scopolamine at lower concentration (less than 0.2 mM) into treatment medium was observed to reduce the root growth as well as the hyoscyamine and scopolamine production. Combination of l-phenylalanine with putrescine appeared the best precursor for both hyoscyamine and scopolamine production.